Globalisation and its impact on wage structure in Singapore. - Oh, Poh Huat. (2008)
The issue of income disparity has been a widely debatable issue in the last few decades and this problem of inequalities is not only evident between countries, but also within countries, with negative consequences on jobs and wages. Some have attributed it to globalization. This paper examines the impact of changes in globalization, in particular to foreign labour, foreign direct investment and trade openness on the income inequality in Singapore and further looks into the impact of the explanatory variables into each individual industry. From the regression, the impact of globalization on income inequality on the general economy is inconclusive and this could be due to the offsetting effects among the respective industries and in the second part of our report, we zoomed in our investigation to see if the relationship between globalization and income inequality can be specifically explained by each of the main industries in Singapore. The results showed that the two industries that have been most affected by globalization are the manufacturing and construction. For transport, storage and communications industry, there is no clear conclusive evidence and thus we could not conclude a meaningful relationship between globalization and income inequality.